Gestión de ventas en la Tienda de Ropa Forever 21 en el cantón Vinces, en el periodo 2024. - Sellan Zamora, Xiomara Skarleth (2025)
Sales management in the Forever 21 clothing store in the Vinces canton, for the period 2024, is a company that is dedicated to the commercialization of clothing for ladies and gentlemen, offers a variety of clothing from casual to elegant and is focused on offering good quality clothing, however, in order to offer differentiating attributes, it has faced a competitive environment, in which other clothing stores offer lower quality clothing, but at lower prices, due to this, the capture of potential customers and customer loyalty has become complicated, since a large part of customers prefer price over quality. The comparison technique was used through a comparative matrix focused on price, quality and promotions to identify the degree of competitiveness; in addition, a survey-based analysis was carried out to determine the level of efficiency of sales strategies focusing on customer satisfaction and the effectiveness of promotions; however, it was found that although consumers value the quality of the garments, the purchase decision is influenced by the pricing strategies of the competitors. It is necessary to implement marketing strategies that improve its position in the local market; these strategies should include more attractive promotions than those of competitors, advertising campaigns and communication oriented to the differential value of the garments, interaction through social networks with its customers, as well as more appropriate loyalty program; by implementing these strategies, the Forever 21 clothing store will be able to expand its visibility in the local market, as well as attract a wider audience and improve the relationship with existing customers, also increase its competitiveness within the local market.